Fast and cost-efficient species identification of Atlantic salmon (Salmo salar L.), brown trout (Salmo trutta), and their hybrids using a single SNP marker - Aykanat, Tutku; Balatsou, Athina; Kähkönen, Kirsi; Syrjänen, Jukka T.; Janhunen, Matti; Leinonen, Tuomas; Prokkola, Jenni M.; Norrgård, Johnny R.; Piccolo, John J. (John Wiley & Sons, 2024)
A workflow for developing a cost- and time-efficient, single nucleotide polymorphism (SNP)-based assay for species and hybrid identification is described. In a reference set (n = 46), the developed assay identified individuals of two closely related species, the Atlantic salmon (Salmo salar L., n = 23) and brown trout (Salmo trutta, n = 23), with 100% accuracy. Furthermore, species and hybrid identification using field-collected embryos had 98.1% concordance (155/158) to more expensive and time-consuming methods that utilized multiple SNP markers. The method can be integrated into management and conservation plans to quantify species' spawning distribution and hybridization rates.
Keywords: conservation genetics; diagnostic locus; hybridization; KASP SNP-assays; species identification